Developmental trajectories of metacognitive processing and executive function from childhood to older age. Issue 11 (November 2020) - Filippi, Roberto; Ceccolini, Andrea; Periche-Tomas, Eva; Bright, Peter
The modern understanding of the term metacognition encompasses two levels of processing: a lower level awareness or knowledge of one's own thoughts and a higher level regulation or control of our thinking. Metacognition, therefore, bears conceptual similarity with executive function: both are concerned with top-down monitoring and control of cognition in the service of ongoing goal-directed behaviour. Previous studies have shown a possible executive function advantage in multilingual speakers but also a possible disadvantage in metacognitive processing. To progress theory on metacognitive processing and the relationship with executive function and linguistic experience across the lifespan, we conducted a study testing 330 healthy individuals in four age groups from 7 to 80 years old. All participants performed a metacognition task and two measures of executive function, which included the Simon task and the Tower of London task. Half the participants were multilingual speakers since birth. We built developmental trajectories of metacognitive and executive function across the lifespan. The best metacognitive efficiency was observed in mid-adulthood, whereas the best executive function processing reached its peak in young adulthood. A steep cognitive decline was observed in older age, while metacognitive efficiency was preserved. Exploratory factor analysis indicated that metacognition and executive function are served by different factors across all ages. Contrary to previous findings in the bilingual literature, a multilinguistic experience conferred neither any significant advantage nor disadvantage in both executive function and metacognitive processing across the lifespan.